Frequency of the HFE C282Y and H63D polymorphisms in Brazilian malaria patients and blood donors from the Amazon region - Torres, F. R. [UNESP]; Souza-Neiras, W. C. [UNESP]; D'Almeida Couto, A. A.; D'Almeida Couto, V. S C; Cavasini, C. E.; Rossit, A. R B; Machado, R. L D; Bonini-Domingos, C. R. [UNESP] (Genetics and Molecular Research, 2008)
Malaria is an endemic parasitosis and its causitive agent, Plasmodium, has a metabolism linked to iron supply. HFE is a gene with the polymorphisms C282Y and H63D, which are associated with a progressive iron accumulation in the organism leading to a disease called hereditary hemochromatosis. The aim of the present study was to determine the allelic and genotypic frequencies of the HFE gene polymorphisms in malaria patients and blood donors from the Brazilian Amazon region. We screened 400 blood donors and 400 malaria patients for the HFE C282Y and H63D polymorphisms from four states of the Brazilian Amazon region by polymerase chain reaction and restriction fragment length polymorphism analysis. We did not find any C282Y homozygous individuals, and the only five heterozygous individuals detected were from Pará State. The most frequent genotype in the North region of Brazil was the H63D heterozygote, in both study groups. Our results contribute to the concept that the Brazilian Amazon region should not be regarded as a single entity in South America. These polymorphisms did not influence the symptoms of malaria in the population studied, as neither severe signs nor high parasitemia were observed. Therefore, different hereditary hemochromatosis diagnostic and control measures must be developed and applied within its diverse locations. Investigations are currently being carried out in our laboratory in order to determine the importance of the coexistence of hereditary hemochromatosis in patients affected by parasitic diseases, such as malaria. ©FUNPEC-RP.
Keywords: Blood donors; Brazilian Amazon region; HFE gene polymorphisms; Malaria; aspartic acid; cysteine; histidine; iron; tyrosine; adult; allele; blood donor; Brazil; female; gene; gene frequency; genetic polymorphism; hemochromatosis; heterozygote; HFE gene; human; major clinical study; malaria; male; parasitemia; Plasmodium; polymerase chain reaction; restriction fragment length polymorphism; symptom; animal; blood; case control study; comparative study; endemic disease; genetics; parasitology; Plasmodium falciparum; Plasmodium vivax; prevalence; Adult; Alleles; Animals; Blood Donors; Case-Control Studies; Endemic Diseases; Female; Gene Frequency; Heterozygote; Humans; Male; Polymorphism, Genetic; Prevalence